Cover Image. (18th August 2021) - Foster, Stephanie L.; Galaj, Ewa; Karne, Saumya L.; Ferré, Sergi; Weinshenker, David
Abstract : The cover image is based on the Original Article Cell‐type specific expression and behavioral impact of galanin and GalR1 in the locus coeruleus during opioid withdrawal by Stephanie L. Foster et al., https://doi.org/10.1111/adb.13037 .